2018
DOI: 10.1186/s12954-018-0263-5
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on HIV pre-exposure prophylaxis (PrEP) utilization and related intervention needs among people who inject drugs

Abstract: BackgroundAntiretroviral pre-exposure prophylaxis (PrEP) is clinically efficacious and recommended for HIV prevention among people who inject drugs (PWID), but uptake remains low and intervention needs are understudied. To inform the development of PrEP interventions for PWID, we conducted a qualitative study in the Northeastern USA, a region where recent clusters of new HIV infections have been attributed to injection drug use.MethodsWe conducted qualitative interviews with 33 HIV-uninfected PWID (hereafter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 55 publications
4
82
0
Order By: Relevance
“…cost) that have been documented in MSM populations [31,32]. Other studies support high acceptability of PrEP among PWID but note competing health priorities, including substance use disorders and need for treatment, as impediments to PrEP engagement [35].…”
Section: Plos Onementioning
confidence: 98%
“…cost) that have been documented in MSM populations [31,32]. Other studies support high acceptability of PrEP among PWID but note competing health priorities, including substance use disorders and need for treatment, as impediments to PrEP engagement [35].…”
Section: Plos Onementioning
confidence: 98%
“…Of note, the disparity in PrEP clinic density in Southern USA also contradicts need in terms of underrepresentation in areas with lower income, higher Black and Latinx/Hispanic populations, and less insurance coverage [82]. Another barrier to PrEP access at the healthcare system level is limited delivery of PrEP to difficult-to-reach populations, such as PWID and homeless individuals, on account of inadequate infrastructure, which will need to be addressed through innovative strategies [83,84].…”
Section: Lack Of Access To Medical Care As a Barrier To Prep Uptakementioning
confidence: 99%
“…Negative experiences with healthcare providers was identified as a barrier to PrEP use [84] Age b Cross-sectional data from an ongoing cohort study of young sexual-minority men in New York City (N = 492)…”
Section: History Of Substance Abusementioning
confidence: 99%
See 1 more Smart Citation
“…Given that outreach efforts to expand PrEP awareness have not included PWID as much as other groups, and as a result non-GB PWID may not view PrEP as a treatment for themselves, we suggest that GB male PWID may have received information about PrEP through gay networks. Past research with PWID found that PWID viewed PrEP for MSM, not for PWID (Bazzi et al, 2018;Biello et al, 2018). We suggest that GB male PWID, given the important intersection of both injection drug use and sexual identity, may function as bridges for the wider diffusion of PrEP among and through PWID social networks (Rogers, 2010;Valente, 1995).…”
Section: Gay and Bisexual Identitymentioning
confidence: 70%